Transition radiation on a dynamic periodic interface - Mkrtchan (Mkrtchyan) A. R. Alpik Rafaelovich; Potylitsyn A. P. Alexander Petrovich; Kocharian (Kocharyan) V. R. Vagan Rashidovich; Saharian A. A. (2016, 2016)
Title screen